Growth, feed utilization and endocrine responses in Atlantic salmon (Salmo salar) fed diets added poultry by‐product meal and blood meal in combination with poultry oil. (7th October 2014) - Hatlen, B.; Jakobsen, J.‐V.; Crampton, V.; Alm, M.; Langmyhr, E.; Espe, M.; Hevrøy, E.M.; Torstensen, B.E.; Liland, N.; Waagbø, R.
Abstract The suitability of land animal by‐products (ABPs) in feed for Atlantic salmon postsmolts (initial weight 372 g) in sea water was studied in a feeding experiment, using poultry by‐product meal (PBM) and porcine blood meal (BM) as protein sources and poultry oil as fat source. Four extruded feeds were tested in a 2 * 2 factorial model, with or without ABP protein sources and with or without poultry oil. The control feed contained a mix of marine and plant ingredients. Initial feed intake was highest in the ABP protein‐based diets, whereas poultry oil had a weak opposite effect. No differences were seen in growth rate or body weight. Addition of PBM and BM led to increased FCR, and lower retention of crude protein and energy. This could be explained by lower digestibility of amino acids and crude protein, and a slightly lower energy level in these diets. Reduced igf1 mRNA levels in liver and muscle were seen in fish fed dietary ABP protein and oil. Despite lower protein digestibility of ABP protein, this study confirms the suitability of ABP protein and lipid in combination with plant ingredients in feed for Atlantic salmon growers.